Pensar la educación desde los derechos: derecho a la igualdad, a disentir y al afecto - Angulo Rasco, José Félix (2024)
The objectives of this brief work are linked to discussing, exposing and modestly making visible some of the most urgent threats that characterize our era, which we can call the Anthropocene that endanger our life on the planet and its ecosystems, on the one hand, and, on the other, the weakening of welfare and political states and the social coexistence, that require democratic coexistence in a just society. Both threats and serious problems are largely caused by ferocious or cannibalistic capitalism. The political, economic and legal framework that enables, allows and accentuates these two great threats to natural and social life in our common home is global neoliberalism, led by the right-wing conservative politics to which I briefly allude. Searching for possible solutions requires rethinking education from its telos in its deepest sense and beginning to change the discourses and approaches that we can use.